KRITIK IBRAHIM M. ABU RABI’ ATAS PERSEPSI ISLAMOFOBIA BARAT - Almas, Afiq Fikri (Living Islam: Journal of Islamic Discourses, 2024)
Islamophobia symptoms significantly emerged among Westerners after the attack on the World Trade Center in the United States on September 11, 2001. Furthermore, the gap between the ideals of Islam as a religion of peace and the Western perception of Islam as a violent religion has become an issue that needs addressing. This research employs a qualitative method based on literature sources, focusing on the thoughts of Ibrahim M. Abu Rabi’, who proposes an approach in religious studies to correct Islamophobia. The research is conducted through literature sources, documents, archives, and similar materials. Ibrahim M. Abu Rabi’ emphasizes the importance of studying Islam through historical and sociological religious approaches. Through the "historical" approach, the study and empirical-historical-critical religious approach are expected to reduce the levels and intensity of violence and tension among religious believers, although not claiming to eliminate them entirely. Ibrahim M. Abu Rabi’ also recommends the necessity of dialogue between Islam and the West. This dialogue, indirectly, will revive the tradition of intellectualism that is free, dialogic, innovative, creative, and egalitarian between these two compass points. Keyword: Ibrahim M. Abu Rabi’, Historical Approach, Religious Sociology   Gejala Islamophobia banyak muncul dari orang-orang barat setelah terjadinya serangan terhadap WTC di Amerika Serikat pada 11 September 2001. Selain itu kesenjangan antara cita-cita Islam sebagai agama perdamaian dengan konteks kehidupan Islam yang dipandang oleh barat sebagai agama kekerasan sudah menjadi isu yang muncul dan harus diselesaikan. Penelitian ini dengan metode kualitatif yang berdasarkan sumber kepustakaan terhadap pemikiran Ibrahim M. Abu Rabi’ yang menawarkan pendekatan dalam kajian keagamaan untuk meluruskan Islamofobia. Penelitian dilakukan melalui sumber pustaka, dokumen, arsip, dan lain sejenisnya. Ibrahim M. Abu Rabi’ menekankan pentingnya kajian Islam melalui pendekatan historis dan sosiologi keagamaan. Melalui pendekatan “historis”,studi dan pendekatan agama yang bersifat empiris-historis-kritis diharapkan mampu mengurangi kadar dan intensitas kekerasan dan ketegangan antara sesama pemeluk agama, tentu tidak juga berpretensi untuk menghilangkan sama sekali. Ibrahim M. Abu Rabi’ juga merekomendasi pentingnya dialog antara Islam dan Barat. Dialog ini secara tidak langsung akan menghidupkan kembali tradisi intelektual yang bebas, dialogis, inovatif, kreatif sekaligus egaliter antara kedua arah mata angin ini. Kata kunci: Ibrahim M. Abu Rabi’, Pendekatan Historis, Sosiologi Keagamaan